Susan Braatz from FAO talks about the "ALL Forest Day" - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Susan Braatz, Senior Forestry Officer ( Forest and Climate Change), FAO (Food and Agriculture Organization) talks about the All Forest Day at COP18 in Doha. Video by Meerim Shakirova, social media reporter